Lost boy : the true story of Captain Hook - Henry, Christina, 1974- (Berkley, 2017)
"From the national bestselling author of Alice comes a familiar story with a dark hook--a tale about Peter Pan and the friend who became his nemesis, a nemesis who may not be the blackhearted villain Peter says he is ..."--